EVALUASI PROGRAM DIKLAT PEMERIKSAAN KINERJA PADA BADIKLAT PEMERIKSAAN KEUANGAN NEGARA BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA - Juliandari, Rhisma; Warsono, Hardi; Sunu Astuti, Retno (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The performance inspection training program is one form of technical training from several training programs contained in the BPK RI PKN Badiklat. The performance inspection training program aims to carry out performance inspection steps starting from the planning process, implementation to reporting according to applicable standards and guidelines. This research aims to analyze the success of the performance inspection training program at Badiklat PKN BPK RI and analyze the driving and inhibiting factors of the training and training program for performance inspection at Badiklat PKN BPK RI using the CIPP (Context, Input, Process and Product) evaluation theory model and three theories of program success according to William N. Dunn (Effectiveness, Adequacy and Accuracy). The descriptive quantitative method is the method used in this research using data collection techniques through distributing questionnaires and interviews. The results of this research indicate that the performance inspection training program is good based on the perceptions of training participants from context indicators with environmental support, input and process with indicators of effectiveness, adequacy and accuracy of resource aspects in implementing the training program. The product or evaluation results in the research also show good value in the quality (output) of training implementation and the performance inspection training program has use value or benefits for the training work unit in the field of work, especially performance inspection (outcome). The driving factors consist of the BPK Strategic Plan for 2020-2024, support from work units and service leaders as well as the leadership of the BPK RI PKN Education and Training Agency, adequate budget allocation and technology (LMS). Inhibiting factors, namely limited internal resources, mismatched schedules in organizing training, competition with other programs and internet down.